Challenges of the Young Generation in the Current of Hedonism and Its Relationship with Pancasila - Saroh, Siti (Jurnal Scientia Indonesia, 2017)
The young generation has interesting topics to support, where in the life of the younger generation there will be interesting dynamics of life to learn. Young people who certainly have a young age are also in an emotionally unstable situation. The various dynamics of life of the young generation that are often discussed is a matter of hedonism. Most young people may not know the dangers of hedonism behavior. Cultural changes due to the behavior of hedonism have become commonplace that are considered normal. Indonesia as a country that makes Pancasila as the basis of the state should apply all values contained in the Pancasila in everyday life. According to (KBBI) Hedonism is a view that considers material pleasure and enjoyment as the main goal in life. If the youth is immersed in this thought, it will certainly harm themselves and others. (Reihan, 2019) shares five ways to avoid the nature of hedonism, namely learning minimalist life, wisely in social media play, setting priorities, don't always look up, selectively choose friends. Besides that, Pancasila as a guideline of course can overcome this problem of hedonism. (Suprayogi, 2018, p. 220) states that the Pancasila as Weltanschauung nation and state life must be taught to the younger generation. This if done will help foster a nationalist sense and make Pancasila a guideline in everyday life.